Anti-Tuberculosis Activity of Extract Ethyl Acetate Kenikir Leaves (Cosmos caudatus H.B.K) and Sendok Leaves (Plantago Major L.) By In Vitro Test - Tatang Irianti; Sylvia Utami Tanjung Pratiwi; Kuswandi Kuswandi; Nanan Tresnaasih; Dharmastuti Cahya; Fatmarahmi Fatmarahmi; Yulia Paramitha (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
The increasing therapy problem including multidrug-resistant tuberculosis (TB) has made it important to discover a new anti-TB drug candidate. The aim of this study was to acknowledge the activity of ethyl acetate extracts of kenikir (Cosmos caudatus H.B.K) and sendok (Plantago major L.) leaves against Mycobacterium tuberculosis (M. tuberculosis) H37Rv. This research used Middlebrook (MB) 7H9 media and observed the growth of M. tuberculosis using Lowenstein Jensen (LJ) media. The concentration of extracts were 0.25 mg/ml, 0.50 mg/ml, and 1.00 mg/ml. The result of this study showed that ethyl acetate extracts exhibited anti-TB activity in 1000 µg/ml of both extracts. The active compound group was detected by thin layer chromatography (TLC) and the separation of compounds was shown by retardation factor (Rf) and the color of the spots. Based on TLC chromatograms, it is known that there are types of compounds, such as ortho-dihydroxy compounds, phenolic compounds, and compound leads to terpenoids for both extracts.